The Effectiveness of Using Role Play to Improve Speaking Skills for Students of Senior High School - Rakasiwi, Audy Krisnandyaz; Wahyuni, Sri; Yosephin W.L, Maria (Edusia: Jurnal Ilmiah Pendidikan Asia, 2024)
The following subjects were specifically investigated in this study; 1) To compare role play learning strategies and conventional models in improving students' English speaking skills. 2.) To find out why the role play learning strategy in improving students' english speaking skills can be said to be more effective. The design of this research is quasi-experimental using control and experimental classes. The method that will be used in the experimental class is the use of Role Play and the control method uses the conventional method. The sample that will be taken by the researcher is two classes from class XI MIPA 2 as the control class and class XI MIPA 5 as the experimental class. To find out the comparison between the experimental class and the control class, the average post-test results in each class will be calculated. To determine the level of effectiveness of roleplay learning, a gain score technique will be used. Based on the results of the assessment obtained from the post-test, the average of control class was 67,64 and experiment class was 71,11. Based on the calculation using the Gain Score formula with reference to the previous data, the Gain Score obtained is 0.72 which is included in the "High" criteria. Some students believed that studying would be more enjoyable if they used roleplaying. Furthermore, it is necessary to develop a roleplay learning strategy to be able to improve students' cognitive abilities as seen from students' English learning outcomes.